Evaluation of environmental impact management control for linear development with reference to ISO 14001 - Geeringh, John Henry (North-West University (South Africa), 1997)
This study resulted from difficulties in containing environmental impacts during the construction phase, as well as subsequent operation and maintenance of Transmission Lines. Impacts identified during the Environmental Impact Assessment (EIA) occurred, notwithstanding the compilation of an Environmental Impact Management Plan (EIMP), to control these impacts and proposed mitigation measures to alleviate the foreseen impacts. A possible reason for this failure is sought by investigating current literarure and practise pertaining to environmental management during construction/maintenance projects in South Africa, with particular reference to Eskom. The term Environmental Management Plan (EMP) has only been in existence since 1990 in the draft Guidelines for Integrated Environmental Management (IEM) of the Department of Environmental Affairs and Tourism (DEAT). A survey of literattJre in South Africa highlighted the fact that very little specific literature pertaining to linear EMP's exist. A search on the Internet also highlighted a total lack of specific literattJre for linear EMP's. The lack of specific standards or guidelines for the compilation of such EMP's, especially on linear developments, and only scant reference to site specific EMP's such as Environmental Management Programme Reports (EMPR's) for mining operations, is one of the major constraints identified during this sttJdy. EIMP's within the Eskom Transmission Group are usually compiled based on the practical experience from previous developments, and regularly the same problems would arise. The continuation and forward feed of information collected during the EIA would take place, but the implementation would somehow fail. This is seen to be caused by a few major factors: • Lack of standards for compilation of EIMP's • Lack of identifying all environmental aspects and associated impacts • Lack of clear objectives and targets • Lack of environmental awareness and training V • Lack of commitment to continual improvement through review of past and existing practises • Lack of commitment to Environmental Management on the part of the Contractor • Lack of an EMS on the part of Eskom Transmission The ISO 14001 Standard for Environmental Management Systems was used as the measurement tool for the compilation and implementation of an Environmental Impact Management Plan. Although only scant reference to such a plan or programme is found in the ISO 1 4001 documentation, the management plan or programme should be seen as an extension of the Environmental Management System (EMS). It is thus necessary to incorporate the elements of an EMS in an EMP, for such a plan or programme to succeed. These elements will then ensure that the EMP falls within the scope of the EMS of the company. The conclusion of this study is that without a proper EMS in place, to form the framework within which to work, the compilation, aims and implementation of a Transmission EIMP would short of its intended effect. This is particularly the case within the Eskom Transmission Group, as the Eskom EMS was never really implemented in this group. The EIMP should in itself be a management system with checks and balances as well as clear objectives and measurable targets. For the purpose of construction, the objective clearly is to prevent and minimise possible negative impacts, rather than managing the environmental damage once it occurred. The EIMP should be adequate enough to impose prevention measures pertaining to environmental damage during construction and subsequent maintenance. An inadequate EIMP inevitably leads to contractual problems and effectively negates the benefits of sound environmental planning that can be derived from the IEM process and good EIA practise. It should form part of the contractual agreement to ensure legal liability, therefore the contract should not be placed before the EIMP is completed. Based upon this study it is recommended that the EIMP be compiled within the framework of an EMS such as ISO 1 4001. All the elements of the EMS should be included in the EIMP to ensure a document which can withstand the pressures of purely development orientated thinking. The principles of integrated environmental planning should at all costs be included in the EIMP and enforced during the construction and maintenance phases of linear developments in Transmission. The final recommendation is that for Transmission purposes, this document should be called the Environmental Management Programme (EMP), as stipulated in ISO 14001, rather than an EIMP. It should be an extension of the EMS. This would ensure environmental management throughout the life-cycle of the project. Once construction of a project is completed and maintenance starts, the EMP should still be the basis for environmental management, within the framework of the Eskom EMS. This would ensure a separate EMP for each asset, and would inevitably lead to better overall environmental management in the Transmission Group.
MSc, North-West University, Potchefstroom Campus